A layered antiferromagnetic semiconductor EuMTe3 (M = Bi, Sb). Issue 12 (6th November 2015) - Niu, Ying Y.; Wu, Dong; Shen, Liang; Wang, Biao
Abstract : We synthesized ternary tellurides EuMTe3 (M = Bi, Sb) using a low‐temperature flux method. These compounds crystallize in the P mmn space group with layered structure. A superstructure modulation along the b ‐axis was observed. Physical property measurements revealed that these compounds are antiferromagnetic semiconductors. Finally, a strong spin–orbit coupling with possible novel quantum interference between localization and weak antilocalization effects was suggested in the present system. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : A new antiferromagnetic semiconductor material, EuMTe3 (M = Bi, Sb), is reported for the first time. These compounds crystallize in the Pmmn space group with layered structure consisting of Te sheets and M/Eu/Te slabs. At low temperature and magnetic field, an abnormal positive magnetoresistance (MR) followed by a large negative MR at higher magnetic fields was detected, rendering a complex effect between spin–orbit coupling and magnetic interactions.